What is Benefit Sharing? Respecting Indigenous Rights and Addressing Inequities in Arctic Resource Projects - Emma Wilson (Resources, 2019)
International standards refer to Indigenous peoples’ right to benefit from resource development, participate in decision-making and determine priorities in development planning that directly affects them. While good practice exists in benefit sharing, Indigenous peoples still lack opportunities for a meaningful role in strategic planning. In his role as UN Special Rapporteur on the Rights of Indigenous Peoples, James Anaya identified a ‘preferred model’ of resource development in which Indigenous peoples have greater control over planning decisions and project implementation, and consequently a more meaningful share of the benefits of resource development. This paper explores the requirements of international standards and guidance alongside different models of benefit sharing in practice by extractive industries in Arctic and sub-Arctic contexts. It is based primarily on desk-based analysis of international hard and soft law and industry standards, while also drawing on ethnographic field research in Russia and Norway. It highlights good practice within mainstream development scenarios and identifies models of benefit sharing that represent a greater degree of Indigenous participation and control. It concludes that there is a need to consider benefit sharing within an overall paradigm that allows greater space for Indigenous voices in decision making, including at the strategic planning stage.